The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1536/ihj.19-117
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin, a DPP-4 Inhibitor, Attenuates Endothelial Dysfunction and Atherogenesis in Nondiabetic Apolipoprotein E-Deficient Mice

Abstract: Dipeptidyl peptidase-4 (DPP-4) inhibitors are novel antidiabetic agents with possible vascular protection effects. Endothelial dysfunction is an initiation step in atherogenesis. The purpose of this study was to investigate whether vildagliptin (Vilda) attenuates the development of endothelial dysfunction and atherosclerotic lesions in nondiabetic apolipoprotein E-deficient (ApoE −/−) mice. Eight-week-old nondiabetic ApoE −/− mice fed a Westerntype diet received Vilda (50 mg/kg/day) for 20 weeks or 8 weeks. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…In a point of view of clinical setting, the dose what we used (50 mg/kg) was high. In previous basic studies using murine model, vilda was administered 5-50 mg/kg by oral gavage [14,15]. We chose higher dose treatment to clarify pleiotropic effect of this drug in addition to antidiabetic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a point of view of clinical setting, the dose what we used (50 mg/kg) was high. In previous basic studies using murine model, vilda was administered 5-50 mg/kg by oral gavage [14,15]. We chose higher dose treatment to clarify pleiotropic effect of this drug in addition to antidiabetic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The DPP-4 inhibitor vildagliptin (vilda) used in this study was provided by Novartis Pharma AG (Basel, Switzerland). For in vivo studies, we used a dose of 50 mg/kg/day of vilda [14,15]. Vilda was given to mice by oral administration using a feeding needle for 4 weeks, beginning at 17 weeks of age.…”
Section: Reagentsmentioning
confidence: 99%
“…Overall, these findings suggest that vitamin D and DPP-4i administered together exert anti-inflammatory and immunomodulatory actions to a greater extent than vitamin D or DPP-4i administered alone. Moreover, VIDPP-4i may exert protective effects against endothelial dysfunction [97,98], which has been shown to play an important role in COVID-19 pathophysiology [10]. Figure 1 illustrates the potential protective effects of VIDPP-4i against SARS-CoV-2 infection and COVID-19 progression to the hyperinflammatory state and cytokine storm.…”
Section: Proposed Synergistic Effects Of Vitamin D and Dpp-4 Inhibitors In Covid-19mentioning
confidence: 99%
“…PACAP also has vasorelaxant effects, and, similarly to substance P, improves vascular endothelial growth factor levels [ 165 , 166 ]. Interestingly, vildagliptin, a DPP4i, was recently shown to inhibit the development of endothelial dysfunction and to prevent atherogenesis in non-diabetic apolipoprotein E–deficient mice [ 167 ]. In addition, Ma et al reported that saxagliptin, another DPP4i, suppressed oxidised low-density lipoprotein cholesterol (ox-LDL)-induced endothelial dysfunction in human vascular endothelial cells, by inactivating JNK, AP-1 and NF-κB signalling [ 168 ].…”
Section: Glucose-lowering Medicationsmentioning
confidence: 99%